2022
DOI: 10.3390/ijms23105833
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Exposure Effects of the Environmental Endocrine Disruptor Benzo(a)Pyrene on Thyroid Axis Function in Zebrafish

Abstract: Benzo(a)Pyrene (BaP) is one of the most widespread polycyclic aromatic hydrocarbons (PAHs) with endocrine disrupting properties and carcinogenic effects. In the present study, we tested the effect of BaP on thyroid development and function, using zebrafish as a model system. Zebrafish embryos were treated with 50 nM BaP from 2.5 to 72 h post fertilization (hpf) and compared to 1.2% DMSO controls. The expression profiles of markers of thyroid primordium specification, thyroid hormone (TH) synthesis, hypothalamu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…B­[ a ]P exposure significantly decreased the circulatory concentrations of T3 and T4 and increased the circulatory concentrations of thyroid-stimulating hormone in the treated rats and fish. , Another study suggested that the primary toxic effects of short-term exposure to B­[ a ]P in zebrafish was compromised hypothalamic-pituitary function, which would then hamper the adequate functional maturation of thyroid follicles and TH synthesis. The main toxic effect of short-term exposure to B­[ a ]P in zebrafish is impaired hypothalamic-pituitary function, which prevents the full functional maturation of thyroid follicles and hormone synthesis . BDE-47 exposure in vivo can alter the secretion of thyroid hormones and change the status of thyroid gland in rats and fish. Elevated serum T3 levels after exposure to BDE-47 in rats are consistent with an epidemiological study showing that plasma concentrations of BDE-47 in adults are positively correlated with serum T3 levels. , A systematic review suggests that exposure to PBDEs and the interaction of PBDEs (or their metabolites) with the TH transport system or thyroid receptors may lead to increased T4 metabolism and excretion .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…B­[ a ]P exposure significantly decreased the circulatory concentrations of T3 and T4 and increased the circulatory concentrations of thyroid-stimulating hormone in the treated rats and fish. , Another study suggested that the primary toxic effects of short-term exposure to B­[ a ]P in zebrafish was compromised hypothalamic-pituitary function, which would then hamper the adequate functional maturation of thyroid follicles and TH synthesis. The main toxic effect of short-term exposure to B­[ a ]P in zebrafish is impaired hypothalamic-pituitary function, which prevents the full functional maturation of thyroid follicles and hormone synthesis . BDE-47 exposure in vivo can alter the secretion of thyroid hormones and change the status of thyroid gland in rats and fish. Elevated serum T3 levels after exposure to BDE-47 in rats are consistent with an epidemiological study showing that plasma concentrations of BDE-47 in adults are positively correlated with serum T3 levels. , A systematic review suggests that exposure to PBDEs and the interaction of PBDEs (or their metabolites) with the TH transport system or thyroid receptors may lead to increased T4 metabolism and excretion .…”
Section: Discussionsupporting
confidence: 55%
“…The main toxic effect of short-term exposure to B[ a ]P in zebrafish is impaired hypothalamic-pituitary function, which prevents the full functional maturation of thyroid follicles and hormone synthesis. 31 BDE-47 exposure in vivo can alter the secretion of thyroid hormones and change the status of thyroid gland in rats and fish. 9 11 Elevated serum T3 levels after exposure to BDE-47 in rats are consistent with an epidemiological study showing that plasma concentrations of BDE-47 in adults are positively correlated with serum T3 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies had shown that polycyclic aromatic hydrocarbons were associated with cancer, immunosuppression, decreased resistance to viral and bacterial infections, and decreased endocrine function. 52 , 53 , 54 , 55 BaP could also inhibit osteoclast formation and bone resorption by binding to aryl hydrocarbon receptor (Ahr), which related to the inhibition of RANKL signal pathway. 56 , 57 Moreover, studies demonstrated BaP inhibited TGF‐β1/SMAD4 and TGF‐β1/ERK/AKT signaling pathways by activating Ahr, thus inhibiting the osteogenic differentiation of BMSC.…”
Section: Discussionmentioning
confidence: 99%
“…Benzo[a]pyrene (BaP) is a typical polycyclic aromatic hydrocarbon, which usually exists in cigarette smoke and smog. Related studies had shown that polycyclic aromatic hydrocarbons were associated with cancer, immunosuppression, decreased resistance to viral and bacterial infections, and decreased endocrine function 52–55 . BaP could also inhibit osteoclast formation and bone resorption by binding to aryl hydrocarbon receptor (Ahr), which related to the inhibition of RANKL signal pathway 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…The working doses of BaP (5 and 50 nM) were used and administered as previously reported by Gao et al and our group [ 19 , 33 ]. For each experiment, pools of 100 embryos were raised in glass petri dish (diam.…”
Section: Methodsmentioning
confidence: 99%